2019
DOI: 10.3991/ijep.v9i4.10201
|View full text |Cite
|
Sign up to set email alerts
|

Organizing Peer Correction in Tertiary STEM Education: An Approach and its Evaluation

Abstract: This article reports on a novel higher-education course format exploiting choreographed peer reviews and self-corrections using an online learning platform. The novel course format aims to reduce teachers' workload as it was motivated by the necessity to run examinations for all courses during all terms, even though almost all courses can only be offered every second term. As a consequence, and because of a very high students-to-teacher ratio, many students have to prepare for examinations without sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…While the STEM Education approach is successful in integrating disciplines in the areas of science and mathematics (Heller & Francois, 2019), it struggles to do so in the areas of language and the arts despite being independent of content. Adjustments were made to overcome the difficulty and the STEAM education approach is being developed to add the element of arts to it so that it does not only integrate science subjects.…”
Section: Discussionmentioning
confidence: 99%
“…While the STEM Education approach is successful in integrating disciplines in the areas of science and mathematics (Heller & Francois, 2019), it struggles to do so in the areas of language and the arts despite being independent of content. Adjustments were made to overcome the difficulty and the STEAM education approach is being developed to add the element of arts to it so that it does not only integrate science subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The overall accuracy of GPT-3.5 (73%) seems to be in line with comparable research on Python tasks (57 to 79%) [24] and to be comparable with student peer reviews where partial incorrect feedback in approx. 14% of the cases [5] or an accuracy of 64% [6] have been reported.…”
Section: Quality Of Gpt-35 In Determining the Submissions' Correctnessmentioning
confidence: 96%
“…Still, incorrect feedback should be avoided, if possible, to prevent confusing novices. For peer reviews, often very short feedback is reported (e.g., median 13-14 words [5,6]). Here GPT-3.5 provides significantly longer feedback with a median of 82 words.…”
Section: Characterization Of the Generated Feedback By Gpt-35mentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of peer review in STEM education are well documented (Heller & Bry, 2019; Li et al 2020; Topping, 2009). In the case of the video assignment, it can help students to narrow their focus or flesh out ideas.…”
Section: Lessons Learnedmentioning
confidence: 99%